Behavior of Reinforced Zero Cement Concrete Slabs under Monotonic Load - Hassoon, Maher Mahmoud; Qissab, Musab Aied (Al-Nahrain Journal for Engineering Sciences, 2024)
Searching for an optimal alternative to normal cement concrete (NCC) is an urgent need nowadays in order to reduce carbon dioxide emissions, reduce energy, and reduce waste materials. Therefore, this research aims to examine zero cement concrete (ZCC) slabs under monotonic loads with several paramedic studies including slab thickness (60mm, 80mm, 100 mm), bar spacing (75mm, 150mm, and 225mm), and molarity concentration (6M, 8M, and 10M). The results showed the behavior of reinforced ZCC slabs is similar to or slightly lower than that of normal cement concrete. Increasing slab thickness from 60 mm to 80 mm and 100 mm enhanced the slab stiffness, increased the applied loads, and reduced the vertical mid-span deflection. Decreasing bar spacing by 33.33% and 66.67% relative to 225 mm reduced also the deflection. The energy absorption was increased due to increasing the slab thickness and bar spacing. When the load increased, the slabs eventually failed by a typically visible punching cone (punching shear).